On Rights-Based Services for People with Disabilities - Nolan, Brian (ESRI, 2003)
The adoption of a rights-based approach in legislation has come to constitute a core element being sought by groups representing people with disabilities and those working with them. This study seeks to contribute to this on-going debate by clarifying some key issues and informing the Irish discussion by a review of some relevant experience elsewhere.